Pemberdayaan Pemuda Dalam Membangun Mentalitas Pemimpin Melalui Pengalaman Tokoh Internasional - Zahrah, Zahrah; Yuliana, Ika; Hafidz, Indriani Puspita; Atma, Wahyu Juni (Kreativasi : Journal of Community Empowerment, 2024)
There are various challenges faced by young people to develop a leadership mentality, therefore it is necessary to develop a tough mentality and be ready to become a leader. Through the Indonesian Youth Diplomacy (IYD) Local Chapter West Nusa Tenggara Goes to School, the title Youth Empowerment in Building a Leader's Mentality Through the Experience of International Figures was published. Goad's training model starts from analyze, design, develop, conduct and evaluate which are included in the preparation, implementation and evaluation process. This method aims to make it easier to interact and communicate. It is hoped that the results of this training activity will provide a deeper understanding of leaders and leadership, students will be able to have the character of a leader and follow in the footsteps of young leaders, as well as the awareness that building a leader's mentality from an early age is very important.